A TYPOLOGY OF SHRINKING CITIES: THE SOCIAL AND ECONOMIC DYNAMIC OF ROMANIAN URBAN NETWORK 2010-2020 - PETROVICI, Norbert; BEJINARIU, Vlad (Studia Universitatis Babeș-Bolyai Sociologia, 2021)
The aim of the paper is to open the issue of multiple shrinkage trajectories in a context of extended urbanisation (Keil 2018) by delineating the different trajectories of Romanian cities. We employed principal component analysis to allow for a multi-criterial classification of Romanian cities based on k-means cluster analysis. Beyond the dominant representation of shrinkage as a process that is mainly correlated with population loss and economic decline, this paper calls for bridging together distinct dimensions which have been either under-studied, such as the aspect of human development, or studied separately across the existing literature, such as governance of shrinkage and economic growth. Therefore, the typology developed here accounts for understanding the process of shrinkage as a complex process, having multiple causes, which determine peculiar trajectories. The outcome confirms the existence of distinct and highly localised shrinkage identities (Martinez-Fernandez, Audirac, et al. 2012). We show that regrowth is not strictly related to the urban core, but it has more to do with a process of complexification of the landscape and social relations existing at the periphery of the city. Shrinking core cities coexists with growing peri-urban areas.